STRATEGI BIMBINGAN ISLAM BERBASIS LIFE SKILL DALAM MEMBENTUK SELF-EFFICACY DAN KEMANDIRIAN SANTRI DI PESANTREN YATIM AL-KASYAF - Rachmasari, Diana; Fajar, Dadang Ahmad; Kusnawan, Aep (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
This study aims to examine Islamic guidance strategies based on life skills in fostering self-efficacy and independence among students at the Yatim Al-Kasyaf Islamic Boarding School. The research scope focuses on three main aspects: planning, implementation, and evaluation of life skill–based Islamic guidance programs designed for orphaned and underprivileged students. A qualitative approach with a descriptive method was employed to capture an in-depth understanding of the guidance strategies applied in the pesantren context. Data were collected through observation, in-depth interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques The findings indicate that the planning of Islamic guidance is systematically structured through the formulation of vision and mission, identification of students’ needs, and the establishment of long-term goals oriented toward strengthening self-efficacy and independence. The implementation is carried out through various life skill activities, including agriculture, livestock farming, entrepreneurship, food and chemical production, waste management, culinary arts, and digital media. These activities are supported by guidance methods such as lectures, learning by doing, discussions, habituation, and mentoring, with counselors serving as moral role models for students. Evaluation is conducted continuously through observation and individual approaches, including corrective actions for students with slower developmental progress. Overall, the study concludes that life skill–based Islamic guidance contributes significantly to the gradual enhancement of students’ self-efficacy and independence, reflected in improved self-confidence, perseverance, responsibility, decision-making ability, and emotional regulation across emotional, behavioral, and cognitive dimensions.